EXPLORING THE IMPACT OF INTERIOR DESIGN ON RESIDENTIAL SATISFACTION IN PREFABRICATED AFFORDABLE HOUSING - Jain, Shubham; Bhandari, Harveen (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explores the influence of interior design on residential satisfaction among residents of prefabricated affordable housing in Delhi, India. The research examines the relationships between three key design dimensions – Spatial Organization (SOR), Visual Elements (VEL), and Indoor Environmental Quality (IEQ) – and overall residential satisfaction (RSA). Findings based on structural equation modelling reveal that all three dimensions have significant positive impacts on RSA. However, Indoor Environmental Quality emerged as the strongest factor, followed by Spatial Organization. Visual Elements, while influential, held a slightly lesser weight in residents' overall satisfaction. These results suggest that residents prioritize practical considerations like thermal comfort, efficient layouts, and sufficient space for activities. This highlights the need for architects and designers to focus on Indoor Environmental Quality and Spatial Organization during the design of prefabricated affordable housing. Careful material selection with low chemical emissions and space-saving solutions are crucial for resident well-being. In conclusion, this research underscores the importance of considering all aspects of interior design to enhance residential satisfaction in affordable housing. Prioritizing Indoor Environmental Quality and Spatial Organization, alongside mindful material selection, can contribute significantly to resident well-being within these dwellings.